PAM variants in patients with thyrotrophinomas, cyclical Cushing’s disease and prolactinomas - De Sousa, Sunita M. C.; Shen, Angeline; Yates, Christopher J.; Clifton-Bligh, Roderick; Santoreneos, Stephen; King, James; Toubia, John; Trivellin, Giampaolo; Lania, Andrea G.; Stratakis, Constantine A.; Torpy, David J.; Scott, Hamish S. (Frontiers in Endocrinology, 2023)
Introduction: Germline loss-of-function variants in PAM, encoding peptidylglycine α-amidating monooxygenase (PAM), were recently discovered to be enriched in conditions of pathological pituitary hypersecretion, specifically: somatotrophinoma, corticotrophinoma, and prolactinoma. PAM is the sole enzyme responsible for C-terminal amidation of peptides, and plays a role in the biosynthesis and regulation of multiple hormones, including proopiomelanocortin (POMC). Methods: We performed exome sequencing of germline and tumour DNA from 29 individuals with functioning pituitary adenomas (12 prolactinomas, 10 thyrotrophinomas, 7 cyclical Cushing's disease). An unfiltered analysis was undertaken of all PAM variants with population prevalence <5%. Results: We identified five coding, non-synonymous PAM variants of interest amongst seven individuals (six germline, one somatic). The five variants comprised four missense variants and one truncating variant, all heterozygous. Each variant had some evidence of pathogenicity based on population prevalence, conservation scores, in silico predictions and/or prior functional studies. The yield of predicted deleterious PAM variants was thus 7/29 (24%). The variants predominated in individuals with thyrotrophinomas (4/10, 40%) and cyclical Cushing's disease (2/7, 29%), compared to prolactinomas (1/12, 8%). Conclusion: This is the second study to demonstrate a high yield of suspected loss-of-function, predominantly germline, PAM variants in individuals with pathological pituitary hypersecretion. We have extended the association with corticotrophinoma to include the specific clinical entity of cyclical Cushing's disease and demonstrated a novel association between PAM variants and thyrotrophinoma. PAM variants might act as risk alleles for pituitary adenoma formation, with a possible genotype-phenotype relationship between truncating variants and altered temporal secretion of cortisol.